Architectural dominants in landscape of Tri-City - Michał Beger (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2017)
Article presents brief description of dominants' role in landscape of cities, definitions used in research. Main goal was to present mentioned objects, their spatial distribution and role performed in landscape. Article presents also: definitions of key terms, delimitation of area being analysed for presence of predominant features, their localization, classification and role performed ind landscape of Tri-City.Also area of study is described, along with its localisation and key spatial characteristics, such as height above sea level, major spatial barriers, along with administrative units.